Autoimmunity-Associated Gut Commensals Modulate Gut Permeability and Immunity in Humanized Mice. (21st March 2019) - Balakrishnan, Baskar; Luckey, David; Taneja, Veena
Abstract: Objective: Although the etiology of rheumatoid arthritis (RA) is unknown, recent studies have led to the concept that gut dysbiosis may be involved in onset. In this study, we aimed to determine if human gut commensals modulate the immune response and gut epithelial integrity in DQ8 mice. Methods: DQ8 mice were orally gavaged with RA-associated ( Eggerthella lenta or Collinsella aerofaciens ) and non-associated ( Prevotella histicola or Bifidobacterium sp.) on alternate days for 1 week in naïve mice. Some mice were immunized with type II collagen and oral gavage continued for 6 weeks and followed for arthritis. Epithelial integrity was done by FITC-Dextran assay. In addition, cytokines were measured in sera by ELISA and various immune cells were quantified using flow cytometry. Results: Gut permeability was increased by the RA-associated bacteria and was sex and age-dependent. In vivo and in vitro observations showed that the RA-non-associated bacteria outgrow the RA-associated bacteria when gavaged or cultured together. Mice gavaged with the RA-non-associated bacteria produced lower levels of pro-inflammatory MCP-1 and MCP-3 and had lower numbers of Inflammatory monocytes CD11c+Ly6c+, when compared to controls. E. lenta treated naïve mice produce Th17 cytokines. Conclusions: Our studies suggest that gut commensals influence immune response in and away from the gut by changing the gut permeability and immunity. Dysbiosis helps the growth of RA-associated bacteria and reduces the beneficial bacteria.